1957
DOI: 10.1177/107769905703400203
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the Mental Health Content of the Mass Media

Abstract: Content categories were developed and used to explore what mass media are saying about mental health problems. Radio and TV samples were found to carry larger percentages of relevant material than newspaper and magazine samples, and certain kinds of attitudes seemed to dominate in all media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

1958
1958
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Preliminary research has indicated that mental illness is a common theme in the mass media (Gerbner, 1961;Gerbner, Gross, Morgan, & Signorielli, 1980;W. Taylor, 1957;Wahl & Roth, 1982).…”
mentioning
confidence: 99%
“…Preliminary research has indicated that mental illness is a common theme in the mass media (Gerbner, 1961;Gerbner, Gross, Morgan, & Signorielli, 1980;W. Taylor, 1957;Wahl & Roth, 1982).…”
mentioning
confidence: 99%
“…The systematic, scientific investigation of portrayals of mental illness in the media began in the late 1950s (Gerbner, 1959;Taylor, 1957). Nunnally (1957) compared the views of mental health experts, the general public, and the mass media.…”
Section: Mental Illness and Television Contentmentioning
confidence: 99%
“…An area of medicine which is often featured in the mass media is mental ill-health (Gerbner, 1961;Taylor, 1957;Wahl & Roth, 1982). Some researchers have cited demonstrable positive effects of viewing programmes that deal with this subject such as mental health education (Edwards, Penick, & Suway, 1973).…”
mentioning
confidence: 97%